VD_FINDINFO HC / 2010 / 172 vom 25. März 2010 - VD Tribunal cantonal (2010)
BAIL À LOYER, LOYER, DEMEURE, EXIGIBILITÉ, EXPULSION DE LOCATAIRE, RÉSILIATION ANTICIPÉE, RÉSILIATION, REJET DE LA DEMANDE | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 274g al. 1 let. a CO, 457 CPC, 23 LPEBL, 7 RULV